Management Strategies of Household Rubbish in Sintang District of West Kalimantan - Paulinus Paulinus; Bagyo Yanuwiadi; Aminudin Afandhi (Indonesian Journal of Environment and Sustainable Development, 2020)
The practice of throwing household rubbish anywhere was currently becoming a community habit which caused several environmental-based diseases. For that matter, it needs a study of the household rubbish management based on the aspect of operational technique, institutional, financing, law/regulations, and community participation. This research aimed to (1) Explain the activity of household rubbish management in Sintang Sub-district. (2) Explain community participation to manage household rubbish, and (3) Arrange a strategy of environmental-based household rubbish management which could be conducted in Sintang Sub-district. This was a descriptive research with a qualitative approach. The research result showed that : (1) The practice of household rubbish management in Sintang District was paying cleanliness retribution but it had no influence on the scattered rubbish management. (2) There was no community participation except to pay cleanliness retribution. (3) The strategy of community-based household rubbish management was conducted by increasing community awareness to pay cleanliness retribution. Community-based integrated rubbish management through sorting organic and inorganic waste starts from the household as the source of waste. Sintang Local Government was suggested to perform community-based integrated rubbish management through a sorting of organic and inorganic waste from the household.Â Â Keywords: Strategy, community participation, management, household rubbish.